THE ROLE OF THE VILLAGE GOVERNMENT IN INCREASING REGIONAL POTENTIAL IN THE SIPOLHA HORIZON VILLAGE, SIMALUNGUN REGENCY - Vincentius Marbun; Siti Hazzah Nur. R (Indonesian Journal of Social Sciences, Policy and Politics, 2025)
Sipolha Horison Village, located in Pematang Sidamanik District, Simalungun Regency, has been designated by the local government as a priority for regional development and tourism along Lake Toba’s shores. Despite this designation, the village continues to face significant challenges in harnessing its regional potential due to limited governmental intervention, particularly at the Local Government level, which serves as the principal administrative actor. This study aims to examine the role of the Local government in developing the regional potential of Sipolha Horizon Village. Employing a descriptive qualitative approach, data were collected through interviews, observations, and documentation, and verified through source and technique triangulation. The findings reveal that the government’s role as regulator is reflected in infrastructure improvements and tourism revitalization efforts; however, the absence of supporting policies undermines its effectiveness. As a catalyst, the government remains insufficient, as evidenced by community dissatisfaction with administrative services and access to information. In its facilitator role, the government has introduced business loan assistance and engaged in private-sector collaborations for farmer group training; however, these measures are still insufficient to support community and regional needs fully. The study concludes that enhancing institutional capacity, establishing stronger regulatory frameworks, and increasing community engagement are crucial to advancing the sustainable development and competitiveness of Sipolha Horizon Village.